Peran Human Relations dalam Menciptakan Lingkungan Kerja yang Inklusif - Dhiyandra Prasetya Gusti; Fauzan Azima; Refky Genta Saputra; Rhizqi Dwiputra Ramadhan; April Laksana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
An inclusive work environment is an important element in supporting employee productivity and well-being in modern organizations. This research aims to explore the role of Human Relations in creating an inclusive work environment, where diversity is respected and every individual feels accepted and supported to develop. Using a qualitative approach with phenomenological methods, this research collects data through in-depth interviews and participant observation of employees from various backgrounds. The research results show that Human Relations has a central role in designing diversity policies, implementing inclusion training, facilitating cross-cultural communication, and handling conflicts related to individual differences. In addition, it was found that support from top management and organizational commitment were key factors in successfully creating an inclusive environment. These findings indicate that effective Human Relations practices can increase employee engagement, reduce turnover, and build a more open and innovative organizational culture. It is hoped that this research can become a reference for organizations in developing Human Relations strategies that focus on inclusion and diversity.